Open and Distance eLearning Readiness of a State University Graduate Students - Ventayen, Randy Joy Magno; Orlanda, Caren Casama (International Journal on Open and Distance e-Learning, 2018)
This paper explored the readiness of the Graduate Students of Pangasinan State University Open University Systems (PSU OUS) to adapt an open and distance learning environment. It also described the story of the PSU OUS and the Province of Pangasinan in embracing the concept of Openness. The study measured self-direction, learning preferences, study habits, technology skills, and computer equipment capabilities of the respondents in terms of readiness as a graduate student. The respondents were the teachers of the Department of Education and other primary school teachers from distant parts of the world who were currently enrolled in PSU OUS taking up Masters or Doctorate degrees. Qualitative methodology was used in data collection techniques. The results of the study indicated that graduate students had a positive attitude towards ODeL. It was recommended that a virtual learning environment be proposed for the benefit of the teachers, the graduate students, and the institution and for contribution to the development of ODeL in the Philippines. It is evident in the Philippines that students and teachers are ready and competent enough to contribute to the changing environment of education.